Perbandingan Yuridis Tanggung Jawab Negara dalam Pemenuhan Hak atas Pangan: Studi Komparatif Program Makan Bergizi Gratis di Indonesia dan Mid-Day Meal Scheme di India - Atiek Pratiwi Putri Naue; Siti Rifqa Raihani; Irsyaf Marsal (Lembaga Yasin AlSys, 2026)
The development of human resource quality through the Program Makan Bergizi Gratis (MBG) constitutes a manifestation of the constitutional responsibility of the welfare state in guaranteeing the fulfillment of the right to food for future generations. However, the implementation of this policy in Indonesia still faces fundamental challenges in the form of a weak juridical foundation that still rests at the level of Peraturan Presiden and a high fiscal burden that places centralized pressure on the State Revenue and Expenditure Budget. This study aims to analyze the weaknesses in the legal basis and fiscal governance of the MBG program in Indonesia through a comparison with the school nutrition system in India. This study used a normative juridical method with statutory, conceptual, and functional comparative approaches, with India’s school nutrition system serving as the main point of comparison. The results showed that India’s success in managing the Mid-Day Meal Scheme is supported by a strong legal framework through the National Food Security Act (NFSA) 2013 as well as the implementation of a proportional cost-sharing scheme between the central government and state governments. Based on these findings, this study offers the “Desentralisasi Asimetris Kesejahteraan” model as a reconstruction of the system in Indonesia through budgetary collaboration between the central and regional governments, which requires revision of the Undang-Undang Pemerintahan Daerah to designate nutrition affairs as a mandatory basic service function. The conclusion of this study emphasizes that strengthening the legal foundation and decentralizing financing are important prerequisites for ensuring the sustainability of the MBG program in a holistic and accountable manner, while also providing a conceptual contribution to the development of food and welfare policy in Indonesia.